Morphology of the Male and Female Personal Names in the River Kosanica Basin - Jašović, Golub M. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
This paper deals with the word formation modes used in construction of male and female personal names recorded in villages located in the river Kosanica basin which is the largest tributary of the river Toplica. Materials for this paper were collected in the period between 1996 and 2006. Recorded onomastic materials belongs to 40 Kosanica villages, from Kuršumlijska Banja, Samokov and Krčmar to southern Kosanica villages Dobri Do, Trn, Trpeze, Sekirača, Vasiljevac and Merdare. More than 2355 male and female personal names have been collected. Our paper has been concerned with morphology and word formation processes which are used in structuring of the male and female personal names in the examined area.
Keywords: speech of Kosanica basin residents; morphology; Serbian personal names